2009
DOI: 10.1021/es803635y
|View full text |Cite
|
Sign up to set email alerts
|

Real Time PCR for the Rapid Detection of vanA Gene in Surface Waters and Aquatic Macrophyte by Molecular Beacon Probe

Abstract: Enterococci serve as an "indicator" of fecal contamination for recreational water quality. The vancomycin-resistant-enterococci (VRE) are emerging environmental contaminants in the surface waters. The aim ofthis study wasto develop a rapid and specific molecular beacon probe (MBP)-based real-time PCR assay for detection of vanA gene in surface waters and aquatic macrophyte. The limit of detection (LOD) of the MBP assay was 1 CFU/mL of VRE [r = 0.943; PCR efficiency = 99.7%] in 2-fold dilution format within 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Recently, Lata et al [31] reported the prevalence of vanA gene (for vancomycin resistance) in surface waters of river Ganga and its tributary and discussed the possible consequences of BPAR, its environmental carriage by plasmid maintenance systems or postsegregational killing (PSK) systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lata et al [31] reported the prevalence of vanA gene (for vancomycin resistance) in surface waters of river Ganga and its tributary and discussed the possible consequences of BPAR, its environmental carriage by plasmid maintenance systems or postsegregational killing (PSK) systems.…”
Section: Resultsmentioning
confidence: 99%
“…A panel of thirteen antimicrobials (antimicrobial abbreviation:mcg/disc) impregnated on paper discs (Himedia Ltd., India) belonging to eight different group of antimicrobials as Fluoroquinolone: Norfloxacin (Nx:10 mcg), β-lactam: Ampicillin (A:10 mcg), Oxacillin (Ox:1 mcg), PenicillinG (P:10 units), Methicillin (M:5 mcg), Aminoglycoside: Gentamicin (G:10 mcg), Streptomycin (S:10 mcg), Tetracycline: Tetracycline (T:30 mcg), Phenicol: Chloramphenicol (C:30 mcg), Macrolide: Erythromycin (E:15 mcg), Rifamycin: Rifampicin (R:5 mcg), Glycopeptides: Vancomycin (Va:30 mcg), Teicoplanin (Te:30 mcg) were used for testing the sensitivity of isolated organisms by Kirby-Bauer disc diffusion test as described by CLSI [31,44]. The diameter of zones showing inhibition were measured to the nearest mm and recorded.…”
Section: Methodsmentioning
confidence: 99%
“…vancomycin resistance and virulence markers such as gelatinase ( gelE ), collagen binding protein ( ace ), endocarditis-associated antigen ( efaA ) and enterococcal surface protein ( esp ), have been explored mostly in clinical settings worldwide (Coque et al 2002 ; Lowe et al 1995 ; Eaton and Gasson 2001 ; Ghoshal et al 2006 ; Mathur et al 2003 ). However, very little is known about the distribution of antimicrobial-resistance and virulence-markers in E. faecalis isolates recovered from river waters (Novais et al 2005 ; Moore et al 2008 ; Lata et al 2009b ). River waters in developing countries are vulnerable to contamination due to discharge of untreated or partially treated municipal and industrial wastes, domestic and wild animal fecal waste and recreational activities on the banks (Ahmed et al 2005 ; Ram et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The qPCR was conducted in a StepOne™ Real-Time PCR System (Life Technologies, Carlsbad, CA) following the conditions previously described (Narciso-da-Rocha et al, 2018) for the ARGs blaTEM, blaCTX and blaOXA-A and the 16S rRNA gene. The qPCR conditions for the detection of the gene vanA were set up in 25 µL volume using the Power SYBR Green mastermix (Thermo Fisher Scientific, Austin, USA) containing 10 µM of each primer: VnF 5'-ATCGGCAAGACAATATGACAGC-3' and VnR 5'-AGCCTGATTTGGTCCACCTC-3' (Lata et al, 2009). The PCR program was initiated by a period of 5 min at 95 °C, followed by 40 cycles of 95 °C for 15 sec and 60 °C for 30 sec.…”
Section: Quantitative Pcrmentioning
confidence: 99%